The astonishing life of octavian nothing, traitor to the nation, volume ii ebook The kingdom on the waves. - Anderson, M. T. (2010)
"A novel of the first rank, the kind of monumental work Italo Calvino called 'encyclopedic' in the way it sweeps up history into a comprehensible and deeply textured pattern." — The New York Times Book Review Fearing a death sentence, Octavian and his tutor, Dr. Trefusis, escape through rising tides and pouring rain to find shelter in British-occupied Boston. Sundered from all he knows — the College of Lucidity, the rebel cause — Octavian hopes to find safe harbor. Instead, he is soon to learn of Lord Dunmore's proclamation offering freedom to slaves who join the counterrevolutionary forces. In Volume II of his unparalleled masterwork, M. T. Anderson recounts Octavian's experiences as the Revolutionary War explodes around him, thrusting him into intense battles and tantalizing him with elusive visions of liberty. Ultimately, this astonishing narrative escalates to a startling, deeply satisfying climax, while reexamining our national origins in a singularly provocative light.